Lizards - Marsh, Laura F. (Washington, D.C. : National Geographic Society, 2012)
Introduces readers to lizards, looking at what they have in common, as well as some of the special traits and abilities that individual species have.
What am I? -- Reptiles -- Scaly skin -- Super lizards -- Mealtime -- Babies -- Legless lizards -- Hide and seek -- Look at me! -- Great escapes -- Biggest and smallest -- Lots of lizards -- What in the world?
OSLIS\Gale Nat Geo eBooks(2/2/23).
Description based on print version record.
Keywords: Lizards -- Juvenile literature; Readers (Elementary); Lizards; Electronic books- OSLIS; Electronic books